1988
DOI: 10.1002/art.1780310311
|View full text |Cite
|
Sign up to set email alerts
|

Renal vascular histology and morphometry in systemic sclerosis. a case–control autopsy study

Abstract: An autopsy case-control study of renal vascular histology and morphometry in systemic sclerosis (scleroderma) was performed. Thirty-five of 70 systemic sclerosis cases had renal tissue available for study: 26 had diffuse cutaneous involvement (9 with "renal crisis" and 17 without) and 9 had limited cutaneous disease (CREST syndrome [calcinosis, Raynaud's phenomenon, esophageal dysmotility, sclerodactyly, telangiectasias]).Age-matched (within 10 years) and sex-matched controls with renal specimens were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 13 publications
0
40
0
4
Order By: Relevance
“…Notably, manifestations of renal disease are observed clinically in up to 50% of SSc patients [5], even if autopsy studies revealed histological evidence of renal impairment in up to 80% of these patients [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Notably, manifestations of renal disease are observed clinically in up to 50% of SSc patients [5], even if autopsy studies revealed histological evidence of renal impairment in up to 80% of these patients [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Chronic changes include reduplication of the glomerular basement membranes, intimal fibrosis with severe luminal narrowing in arteries and arterioles, organization and recanalization of luminal thrombi, interstitial fibrosis, and glomerulosclerosis as a result of chronic ischemic damages. Marked intimal thickening leads to severe luminal narrowing in renal arteries after SRC (9). However, it is difficult to determine the cause of intimal fibrosis without severe luminal narrowing, interstitial fibrosis and glomerulosclerosis, as in the present case, because this pattern of chronic changes may be seen in the chronic stage of TTP, longstanding essential hypertension, and SSc without SRC (9).…”
Section: Discussionmentioning
confidence: 71%
“…Marked intimal thickening leads to severe luminal narrowing in renal arteries after SRC (9). However, it is difficult to determine the cause of intimal fibrosis without severe luminal narrowing, interstitial fibrosis and glomerulosclerosis, as in the present case, because this pattern of chronic changes may be seen in the chronic stage of TTP, longstanding essential hypertension, and SSc without SRC (9).…”
Section: Discussionmentioning
confidence: 71%
“…Although the pathogenesis of scleroderma renal crisis is unknown, endothelial cell injury, leading to narrowing and obliteration of the lumen of the vessels, is the primary pathogenetic mechanism. Vascular damage with arteries wall thickening is present in SSc patients without scleroderma renal crisis [29] . Renal vascular resistance was increased in main, interlobar and cortical vessels of SSc patients with normal renal function when compared with normal controls [30] .…”
Section: Discussionmentioning
confidence: 99%